La Educación Virtual en la Formación Profesional de los Estudiantes de la carrera de Derecho: Las Competencias Técnicas y Legales - López Jumbo, Mario Rodrigo (2024)
Virtual education at the university level has seen an increase in demand in recent times. Thus, this research aimed to identify the effectiveness of didactic resources utilized in virtual education and to establish the technical and legal competencies attained by students in the virtual mode of the Law program for their professional practice. Moreover, this study adopted a qualitative approach, employing a questionnaire distributed via Google Forms and checklists. Among the findings, it was observed that the virtual learning environment utilized by the Law program facilitates virtual meetings and online assessments, with forums being the most utilized asynchronous resource. Concerning technical competencies, it was found that 55% of students are proficient in digital applications, while only 18% utilize virtual libraries. Regarding legal competencies, students have acquired competencies in analyzing and interpreting legal norms at a rate of 61%, but there's been insufficient training in the competency of conducting legal processes, with only 12% of students frequently expressing this need. Finally, based on these findings, it is concluded that virtual education in the Law program relies on synchronous and asynchronous resources, fostering the development of various competencies that enable students to attain better professional training. Hence, it is recommended for university institutions to enhance virtual learning environments to optimize the learning process and the acquisition of technical and legal competencies. Keywords: Virtual education; professional training; technical and legal competencies; Law program.